2000
DOI: 10.1023/a:1007551316253
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The effectiveness of a geographical decision support tool (Dragnet) for locating the base of serial offenders was compared across 570 models comprised of a range of negative exponential functions, buffer zone components, and normalization parameters. The models were applied to the body disposal locations within each series for 70 U.S. serial killers. Two normalization parameters were compared for all functions. The test of effectiveness was a specifically defined measure of search cost. When applied to the Dra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 156 publications
(23 citation statements)
references
References 8 publications
0
21
0
2
Order By: Relevance
“…The underlying basis for such strategies is the 'circle hypothesis' which states that a perpetrator who commits a series of crimes leaves their home base, commits a crime, then returns to the home base, and therefore resides within a circle constructed by the diameter of the two incident locations farthest apart (Canter & Larkin, 1993). Studies (Canter et al, 2000;Canter & Larkin, 1993;Kocsis & Irwin, 1997;Snook et al, 2004) have demonstrated evidence for the validity of the circle hypothesis. Formulae for spatial distribution strategies which use the set of incident coordinates in each formula to achieve a centrographic point prediction for the offender residence.…”
Section: Current Methods/systems Of Geographic Profilingmentioning
confidence: 99%
“…The underlying basis for such strategies is the 'circle hypothesis' which states that a perpetrator who commits a series of crimes leaves their home base, commits a crime, then returns to the home base, and therefore resides within a circle constructed by the diameter of the two incident locations farthest apart (Canter & Larkin, 1993). Studies (Canter et al, 2000;Canter & Larkin, 1993;Kocsis & Irwin, 1997;Snook et al, 2004) have demonstrated evidence for the validity of the circle hypothesis. Formulae for spatial distribution strategies which use the set of incident coordinates in each formula to achieve a centrographic point prediction for the offender residence.…”
Section: Current Methods/systems Of Geographic Profilingmentioning
confidence: 99%
“…Popular software like Rigel Analyst, CrimeStat, and Dragnet produce similar outputs, as they are based on a distance decay algorithm (Canter et al 2000;Canter and Hammond 2006;Rich and Shively 2004). After incorporating important offender information (a non-exhaustive list included above), the software places a grid over an area of interest and then calculates the likelihood that the offender's anchor point is within each grid square (Rich and Shively 2004).…”
Section: Criminal Behaviour and The Environmentmentioning
confidence: 99%
“…Example 1: Geographical Criminal Profiling. A guiding concern for geographical criminal profiling is achieving low prediction error, and the field progresses in large part through the competitive testing of diverse models ranging from the centroid method to sophisticated probabilistic models (e.g., Rossmo, 1999;Canter et al, 2000;Snook et al, 2005;Levine and Block, 2011). This seems like an unlikely field to harbor a bias bias, yet the bias/variance perspective appears to be unfamiliar to researchers in this area 2 .…”
Section: Four Examples Of the Bias Biasmentioning
confidence: 99%